Polycystic Ovary Syndrome and NC-CAH: Distinct Characteristics and Common Findings. A Systematic Review - Papadakis, Georgios; Kandaraki, Eleni A.; Tseniklidi, Ermioni; Papalou, Olga; Diamanti-Kandarakis, Evanthia (Frontiers in Endocrinology, 2019)
BACKROUND: Twenty-one-hydroxylase–deficient non-classic adrenal hyperplasia (NC-CAH) is a very common autosomal recessive syndrome with prevalence between 1 :1000 to 1 :2000 individuals and the frequency varies according to ethnicity. On the other hand, polycystic ovary syndrome has a familial basis and it is inherited under a complex hereditary trait. This syndrome affects 6% to 10% of women in reproductive age and it is the most common endocrine disorder in young women. Our aim was to investigate, through a systematic review, the distinct characteristics and common findings of these syndromes. METHODS: The search period covered January 1970 to November 2018, using the scientific databases PubMed. Inclusion criteria were adult women patients with PCOS or NC-CAH. Search terms were “polycystic ovary syndrome”, “PCOS”, “non-classical adrenal hyperplasia”, “NC-CAH”, “21-hydroxylase deficiency”. From an initial 16255 titles, the evaluations led to the final inclusion of 97 papers. RESULTS: The clinical features of NC-CAH are hirsutism and ovulatory and menstrual dysfunction therefore; differentiation between these two syndromes is difficult based on clinical grounds only. Additionally, NC-CAH and PCOS are both associated with obesity, insulin resistance and dyslipidaemia. Reproductive abnormalities are also common between these hyperandrogenemic disorders since in patients with NC-CAH polycystic ovarian morphology and subfertility are present as they are in women with PCOS. The diagnosis of PCOS, is confirmed once other disorders that mimic PCOS have been excluded eg, conditions that are related to oligoovulation or anovulation and/or hyperandrogenism, such as hyperprolactinaemia, thyroid disorders, non-classic congenital adrenal hyperplasia and androgen-producing neoplasms. CONCLUSIONS: The screening tool to distinguish non-classic adrenal hyperplasia from PCOS is the measurement of 17-hydroxyprogesterone levels. The basal levels of 17-hydroxyprogesterone may overlap, but ACTH stimulation testing can distinguish the two entities. In this review these two common endocrine disorders are discussed in an effort to unveil their commonalities and to illuminate their shadowed distinctive characteristics.